Editors' Introduction IDEA at 30: Looking Back, Facing Forward — A Disability Studies Perspective - Jan W. Valle; David J. Connor; D. Kim Reid (Disability Studies Quarterly, 2006)
This special issue of Disability Studies Quarterly is based upon four papers presented at the 5th annual National Conference on Disability Studies in Education (2005) sponsored by Teachers College, Columbia University. The four papers address the 2005 conference theme: The 30th anniversary of IDEA and Its impact on American Schools and Society. In addition, the issue includes eight responses from scholars invited to comment upon these four cornerstone papers. Thus, our introduction to the special issue is divided into four sections that tie together ideas presented in the four major papers and eight responses: (1) IDEA and public opinion (2) IDEA and the institutionalization of ableism and racism; (3) IDEA enactment and consequences; and (4) IDEA resistance and the countering of deficit-based assumptions of disability. We conclude with our reflection upon these ideas as well as a vision of disability studies in education for the next thirty years.